PENGARUH TRANSFER PRICING, LEVERAGE, PROFITABILITY DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Wijaya, Frendyana Adi; Suparmun, Haryo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Abstract: Tax avoidance is a legal act to reduce tax liabilities by exploiting loopholes in tax law. This research aims to determine the influence of transfer pricing, leverage, profitability, company size, capital intensity, independent commissioners, and audit committees on tax avoidance.This research uses 51 manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2021 period. In this research, a purposive sampling method was used and the data analysis method used was multiple regression analysis.The results of this research show that transfer pricing, leverage, company size, capital intensity, independent commissioners, and audit committees do not affect tax avoidance. Profitability shows that the results have a negative effect on tax avoidance. High profitability tends to make companies carry out tax avoidance because the greater the value of a company's ROA, the more management will tend to carry out tax avoidance because management will feel that the tax burden paid by the company is too large even though the company's profits are increasing.